2007
DOI: 10.1007/s10443-007-9046-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Mechanical Properties of Carbon Fiber Reinforced (BC x –SiC) n Multilayered Matrix Composites

Abstract: A boron doped carbon materials (BC x ) was prepared by chemical vapor deposition and a 3D (BC x -SiC) n multilayered matrix composite reinforced by carbon fiber, C/(BC x -SiC) n , was prepared by chemical vapor infiltration (CVI). XPS and SEM results showed that the BC x matrix had a boron content of 15at.% and exhibited a very finely laminated structure. XRD analysis showed the BC x matrix was mainly carbon with B 4 C crystals in it. SEM and EDS results showed that the BC x layers and the SiC layers were depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…6À9,11À14 It is desirable that the mechanisms be understood but it is a much difficult problem which may involve the gas phase reactions (thermodynamics and kinetics), the gas phase diffusions, the nucleations, the surface deposition or surface reactions and the crystal growth. For the carbon rich system (propene þ BCl 3 ) in the gas phase reactions, the experiments have determined the preparation conditions 11,12 as well as the apparent activation energy of 208.7 kJ/mol. 13 In understanding the insights of the reactions, a theoretical study of the thermodynamics 14 and part of the reaction paths 19 were carried out in our group.…”
Section: Introductionmentioning
confidence: 99%
“…6À9,11À14 It is desirable that the mechanisms be understood but it is a much difficult problem which may involve the gas phase reactions (thermodynamics and kinetics), the gas phase diffusions, the nucleations, the surface deposition or surface reactions and the crystal growth. For the carbon rich system (propene þ BCl 3 ) in the gas phase reactions, the experiments have determined the preparation conditions 11,12 as well as the apparent activation energy of 208.7 kJ/mol. 13 In understanding the insights of the reactions, a theoretical study of the thermodynamics 14 and part of the reaction paths 19 were carried out in our group.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture of the matrix and fiber surface was seen clearly on the failed surface. The fractured matrix presents a stepwise feature, caused by the debonding of the interface between the different layers in the matrix and deflection of cracks [10], whereas, there is no obvious stepwise cracks for the composite with monolithic ceramic matrix. No matrix was adhered to the fiber surface and only some matrix particles were left on the surface, implying that the debonding occurred between the fiber and the interface.…”
Section: Interlaminar Shear Strengthmentioning
confidence: 99%
“…Moreover, the multilayered matrix in the composites can undergo microcracking and debonding between the different layers under loading. The cracks formed can be arrested or deflected during their prorogation in the matrix [10,[15][16][17]. The function is same as that of multilayered interface between the fiber and the matrix, and can give toughness to the materials.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lamouroux et al [16] introduced a multilayer SiC-B-C ceramic matrix to a 2.5D preform by pulsed CVI (P-CVI) and found that the multilayered ceramic matrix could improve the oxidation resistance and thermomechanical behavior of the composites. Recently, Yang et al [17] prepared a 3D (BC x -SiC) n multilayered matrix composite reinforced by carbon fiber, and the composite exhibited a remarkable metal-like yield stage and high flexural strength. Xie et al [18] showed that the laminated structure of SiC w -SiC ceramic composites can improve the flexural strength, tensile strength and fracture toughness through whiskers pullout, cracks deflection and bridging between interfacial and inter-laminar zones.…”
Section: Introductionmentioning
confidence: 98%